Attenuating effect of N-acetyl-L-cysteine against acute cocaine toxicity in rat C6 astroglial cells - BADISA, RAMESH B. (D.A. Spandidos, 2013)
Astroglial cells are one of the most abundant cell types in the mammalian brain functioning in neuronal survival and in maintenance of fundamental patterns of circuitry. To date, no study has been conducted regarding the short-term impact of cocaine on these cells in cultures. The present study aimed to investigate acute cocaine (1 h) treatment on cell viability in rat C6 astroglial cells. In addition, the potential effect of N-acetyl-L-cysteine (NAC) against cocaine-induced toxicity was studied. It was observed that 1 h of acute cocaine exposure at 2, 3 and 4 mM caused a dose-dependent decrease in cell viability with an LC(50) of 2.857 mM. Furthermore, cocaine treatment caused a decrease in glutathione (GSH) levels in the cells. It was found that cocaine did not exhibit pro-oxidant activity during its exposure to cells. Acute cocaine exposure did not induce nitric oxide (NO) release in the cells. A 5-point (1–5 mM) dose-response curve of NAC clearly indicated no adverse effect on astroglial cell viability. Pretreatment of cells with 5 mM NAC for 30 min, followed by its discard, and exposure to cocaine (2–4 mM) for 1 h protected cells against cytotoxicity by 90%. Treatment of cells with NAC-cocaine mixture rendered 100% protection. Further investigations revealed that the protection by NAC was through the increased GSH levels in the cells. Our results indicate that decreased GSH levels may represent one of the underlying pathologies of cell death and that antioxidant compounds which increase the GSH production could protect against cocaine-induced toxicity by promoting a pro-survival role in astroglial cells.